Infant temperament and childhood psychiatric disorder: longitudinal study. Issue 2 (3rd April 2013) - Sayal, K.; Heron, J.; Maughan, B.; Rowe, R.; Ramchandani, P.
Abstract Background Temperamental characteristics emerge early in life and can shape children's development, adjustment and behaviour. We aimed to investigate the association between early infant temperament and later childhood psychiatric disorder in a community sample. Methods This prospective, population‐based study used data from the Avon Longitudinal Study of Parents and Children (ALSPAC). In a sample of 7318 children, we investigated whether temperamental characteristics assessed at the ages of 6 months and 24 months are associated with an independent diagnosis of psychiatric disorder ascertained at age 7 years. Results After adjusting for confounders, temperamental characteristics assessed at 6 and 24 months of age were associated with psychiatric disorder at age 7 years. In particular, intensity of emotional reaction at age 6 months was associated with later disorder (adjusted odds ratio = 1.56; 95% confidence interval 1.19, 2.04; P = 0.002). These associations were stronger in girls and in those children with high levels of intensity at both 6 and 24 months of age. Conclusions Temperamental characteristics involving high levels of emotional intensity within the first year of life are longitudinally associated with psychiatric disorder in mid‐childhood, suggesting that the roots of psychiatric disorder may, in some cases, lie very early in life.